Control DC link of single-phase dynamic voltage restorer - Toumi Toufik; Allali Ahmed; Abdelkhalek Othmane; Soumeur Mohammed Amine; Nasri Abdelfatah (International Journal of Applied Power Engineering (IJAPE), 2020)
This paper is aimed to illustrate and expose the performance of single-phase voltage dynamic voltage restorer (DVR) control connected to the electrical distribution grid. This performance is easily expressed by compensating for the sags and the swells voltages, and regulating the voltage across the load by injecting a voltage component in series with the source voltage increased or decreased with respect to the source voltage the load-side waveforms are purely sinusoidal. The integration of serial and chopper converters makes the DVR capable of bidirectional power flow. The key to this topology is its ability to compensate for sagging and swelling of the voltage in the long run. The modeling of the DVR and the design of its controller is included in this document. Effectiveness of control systems and start-up sequence of DVR operation is verified by detailed simulation studies. The control method used in this work is based on the use of a booster chopper and two cascade loopsto generate the PWM command to control the chopper. The effectivenessof the suggested method is confirmed by the MATLAB/SIMULINK® simulation results and some prototype experiments. These results showthe capacity of the proposed DC link control.